2021
DOI: 10.1007/s00247-021-05211-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social distancing during the COVID-19 pandemic on rates of pediatric idiopathic intussusception

Abstract: Background The causes of idiopathic ileocolic intussusception are unknown, with infection as the most likely culprit. Recently, social distancing measures were implemented during the coronavirus disease 2019 (COVID-19) pandemic to decrease transmissible infectious diseases, creating an opportune setting to study the role of infection on the pathogenesis of intussusception on a population level. Objective To investigate the impact of social distancing on intussusception.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Given known reductions in viral infections associated with social distancing and masking practices during the COVID-19 pandemic, we hypothesized that the incidence of intussusception decreased at a national level in 2020 compared to previous and subsequent years. Corroborating our hypothesis are single-center studies that have shown decreases in pediatric intussusceptions during 2020 [ 4 , 5 ]. From the surgical perspective, one study from Tokyo during the height of the COVID-19 pandemic also showed a decrease in emergent pediatric operations, with a statistically significant drop in operations related to intussusception [ 6 ].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Given known reductions in viral infections associated with social distancing and masking practices during the COVID-19 pandemic, we hypothesized that the incidence of intussusception decreased at a national level in 2020 compared to previous and subsequent years. Corroborating our hypothesis are single-center studies that have shown decreases in pediatric intussusceptions during 2020 [ 4 , 5 ]. From the surgical perspective, one study from Tokyo during the height of the COVID-19 pandemic also showed a decrease in emergent pediatric operations, with a statistically significant drop in operations related to intussusception [ 6 ].…”
Section: Introductionsupporting
confidence: 58%
“…With the implementation of mandated social distancing guidelines and mask mandates, the spread of most respiratory infections, including RSV and influenza, decreased in 2020 [ 1 ]. Given that idiopathic intussusception has been hypothesized to be primarily due to viral causes, specifically some of the common childhood viral illnesses such as RSV [ 3 ], as well as smaller studies suggesting this link [ 4 , 5 , 7 ], we hypothesized that a documented decrease in viral infections in 2020 would be associated with a decrease in intussusception at a national level. Our results support this hypothesis with more than 700 fewer diagnoses of intussusception in 2020, the period of maximal implementation of masking and social distancing.…”
Section: Discussionmentioning
confidence: 99%
“…Some later studies also documented that the COVID-19 pandemic and the implementations of preventative measures to combat this communicable disease have notably influenced the epidemiology of intussusception [ 15 , 16 , 17 , 18 ]. Meanwhile, Handa et al demonstrated that social distancing has resulted in a significant decline in intussusception [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some later studies also documented that the COVID-19 pandemic and the implementations of preventative measures to combat this communicable disease have notably influenced the epidemiology of intussusception [ 15 , 16 , 17 , 18 ]. Meanwhile, Handa et al demonstrated that social distancing has resulted in a significant decline in intussusception [ 18 ]. Our study also noted the epidemiological feature of intussusception during the COVID-19 pandemic, in which the number of patients receiving USGHER in 2020 decreased significantly from that in 2019 ( p = 0.042).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation